Criminal man - Lombroso, Cesare, 1835-1909 (e-Duke books scholarly collection., 2006)
Cesare Lombroso is widely considered the founder of criminology. His theory of the "born" criminal dominated European and American thinking about the causes of criminal behavior during the late nineteenth century and the early twentieth. This volume offers English-language readers the first critical, scholarly translation of Lombroso's Criminal man, one of the most famous criminological treatises ever written. The text laid the groundwork for subsequent biological theories of crime, including contemporary genetic explanations--Cover